Analisis Faktor Yang Memengaruhi Keputusan Pengguna E-Commerce Dalam Memilih Jasa Ekspedisi Di Kota Palembang - Rahmah Hamidah; Keti Purnamasari; Kiki Azakia (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The continuous growth in the use of and purchasing transactions on e-commerce platforms has encouraged logistics service providers to compete in marketing their services in order to attract consumers. This study examines the factors that influence e-commerce users’ decisions in selecting logistics service providers for product delivery. A quantitative approach with an associative research design was employed by analyzing independent variables consisting of cost, time, area coverage, and delivery service features, with intention as a mediating variable and user selection decision as the dependent variable.The respondents in this study were e-commerce users in Palembang City. The sampling technique used was non-probability sampling with a purposive sampling method, conducted through the distribution of online questionnaires measured using a Likert scale, supported by secondary data sourced from academic journals, websites, and other relevant sources. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). A total of 247 respondents met the research criteria. The results show that shipping cost and delivery service quality have a positive and significant effect on users’ selection decisions. Meanwhile, time, area coverage, and service features do not have a significant effect, either directly or indirectly. These findings indicate that cost and service quality are the main considerations and play an important role in shaping users’ intentions and decisions, followed by other factors, although their effects are not significant. Theoretically, this study extends existing knowledge by demonstrating causal relationships among factors influencing consumer decisions in choosing logistics service providers. Practically, the findings are expected to serve as a reference for logistics service providers in e-commerce to create new innovations, particularly by offering competitive pricing and continuously improving service quality.